2015
DOI: 10.1016/j.ijsu.2015.07.708
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic laparoscopic cholecystectomy in adult sickle cell disease patients with cholelithiasis: A prospective cohort study

Abstract: Postoperative complications related to SCD were less frequent for asymptomatic patients who had a laparoscopic prophylactic cholecystectomy. This intervention, if performed with perioperative specific management, is safe and helps avoid emergency operations for acute complications including cholecystitis, choledocholithiasis, and cholangitis. For SCD patients, a prophylactic cholecystectomy reduces hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…The incidence of procedure-related complications was minimal and the vast majority of patients progressed satisfactorily after surgery 7, 8. The surgical approaches used are laparotomy and laparoscopy, with most authors considering the latter safer for patients, with less complications related to surgery, shorter operative time and faster postoperative recovery, as well as a shorter hospital stay 10, 11, 12, 13, 14. However, a study published in the International Journal of Surgery in 2009 found a positive relationship between acute chest syndrome and laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of procedure-related complications was minimal and the vast majority of patients progressed satisfactorily after surgery 7, 8. The surgical approaches used are laparotomy and laparoscopy, with most authors considering the latter safer for patients, with less complications related to surgery, shorter operative time and faster postoperative recovery, as well as a shorter hospital stay 10, 11, 12, 13, 14. However, a study published in the International Journal of Surgery in 2009 found a positive relationship between acute chest syndrome and laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most experts, similar to in the hematology service at UFTM, do not recommend surgery before symptoms appear. There is evidence that this profile can be clinically managed for long periods,8, 14 so the medical team usually prescribe antispasmodic agents for minor pain and recommend preventative measures such as a low-fat diet for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and sixty‐eight reports discuss, in variable detail, the perioperative care of SCD patients. A multidisciplinary collaboration and communication between the surgeon, anesthetist, hematologist and blood bank specialist are universally considered to be mandatory, although specific study data is not available to support this unanimous recommendation . When required, the preemptive and planned coordination with an ICU team for post‐operative admission and care is suggested .…”
Section: Resultsmentioning
confidence: 99%
“…The role for antibioprophylaxis is discussed by many, and two strategies seem to co‐exist in the literature. There are authors recommending prophylaxis according to type of surgery, and others adapting it to the individual patients' medical histories . As a standout, splenectomy needs specific considerations, including preoperative immunizations against encapsulated bacteria, as in the context of asplenia .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation